Breaking Boundaries: Advancing Trisulfur Radical-Mediated Catalysis for High-Performance Lithium–Sulfur Batteries - Wu, Junfeng; Zhang, Bohai; Zhao, Zhiqi; Hou, Yuehui; Wang, Yufeng; Zhao, Ruizheng; Zhang, Hao; Hu, Jiandong; Yang, Ke; Tang, Bin; Zhou, Zhen (Nano-Micro Letters, 2025)
Lithium–sulfur batteries (LSBs) have attracted significant attention due to their high theoretical energy density and low-cost raw materials. However, LSBs still face various challenges in practical applications, particularly the shuttle effect, electrode passivation, and slow kinetics. In recent years, trisulfur radicals (TRs), important intermediates in LSBs, have emerged as a promising and beyond-traditional solution to these problems, which serves as a mediated catalyst to improve the electrochemical performance of LSBs. As a system that is inconsistent with the catalytic conversion process discussed in the traditional LSBs, this review focuses on the generation, detection, promotion, and catalytic roles of TRs, especially emphasizing the formation of TRs in solid-state lapis lazuli analogs and discussing the pros and cons of high donor number solvents and/or their co-solvents in stabilizing TRs. Strategies involving homogeneous/heterogeneous catalysts are discussed for increment of TRs and enhancing catalytic reactions in LSBs. Ultimately, given TRs’ significant potential as a key factor in enhancing the performance of LSBs, future perspectives and outlooks are provided to guide the further development of TRs in LSBs. This review provides valuable insights into the design of electrolytes and catalysts for increment of TRs, paving the new practical direction and way for advanced LSBs. Highlights: 1 The review emphasizes the formation of trisulfur radicals in solid-state lapis lazuli analogs and the role of high donor number solvents and/or their co-solvents in stabilizing trisulfur radicals. 2 The detection techniques are also discussed for monitoring the generation of trisulfur radicals, which are critical for understanding their behavior and optimizing the design of lithium–sulfur batteries. 3 The strategies involving both homogeneous and heterogeneous catalysts are summarized to increase the generation of trisulfur radicals and enhance catalytic reactions in lithium–sulfur batteries for practical applications. The strategies involving both homogeneous and heterogeneous catalysts are summarized to increase the generation of trisulfur radicals and enhance catalytic reactions in lithium–sulfur batteries for practical applications.